Sequential injection system for the enzymatic determination of ethanol in wine - Páscoa, Ricardo N. M. J. (2011)
A sequential injection system was developed for the enzymatic determination of ethanol in wine. The spectrophotometric determination is based on the enzymatic reaction catalyzed by alcohol dehydrogenase in the presence of NAD+. The system was applied to the determination of ethanol in a range of 0.008-0.024% (v/v) with good repeatability; RSDn)10 < 2.3%. The results obtained with the developed system showed good agreement with those obtained by using the reference method. The determination rate was 25 h-1; 1 ímol of NAD+, 1.1 units of enzyme, and 50 íL of sample were consumed per determination; and the waste produced was 2.2 mL per assay.